Volume 1: Turbomachinery 1988
DOI: 10.1115/88-gt-59
|View full text |Cite
|
Sign up to set email alerts
|

Flow in Single and Twin Entry Radial Turbine Volutes

Abstract: This paper presents a numerical analysis and experimental measurements of flows in the vaneless volute of a radial–inflow turbine. Cases of single and twin entry to the volute were studied, and in particular the case of unequal flows, or partial admission, to the two entries. The distance between the rotor tip and the limit of the internal wall separating the two flows was varied in order to study the effects of interaction of the two streams. The computational model is based on a quasi–three–di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…• The calculation of the scroll's flow, including the vane support [1,2] • The measurement and calculation of the scroll's flow, without the vane support [3][4][5][6][7][8][9][10][11][12] It is necessary to mention that the present experimental scroll investigations using a stator are mostly carried out without vanes.…”
Section: Symbolsmentioning
confidence: 99%
“…• The calculation of the scroll's flow, including the vane support [1,2] • The measurement and calculation of the scroll's flow, without the vane support [3][4][5][6][7][8][9][10][11][12] It is necessary to mention that the present experimental scroll investigations using a stator are mostly carried out without vanes.…”
Section: Symbolsmentioning
confidence: 99%
“…However, twin-entry turbine flow field investigation under partial admission conditions is rare in open literature. Lymberoppoulos et al [12] published experimental and numerical study on flow field in the twin-entry volute under partial admission conditions. Yeo and Baines [13] performed experimental volute flow field investigation using laser-two-focus velocimeter under full and partial admission conditions of the rotor inlet flow.…”
Section: Introductionmentioning
confidence: 99%
“…Chapple [1] reported that longer and shorter bend lengths reduce the turbine efficiency. The cross section geometry affects greatly the turbine performance as emphasized by Lymberopoulos et al [2]. Up to 1.5 per cent variation in turbine total to total efficiency has been recorded by Barnard and Benson [3].…”
Section: Introductionmentioning
confidence: 99%